Comparison Between Multicomponent Exercise and Walking Interventions in Long-Term Nursing Homes: A Randomized Controlled Trial. (17th December 2019) - Rezola-Pardo, Chloe; Rodriguez-Larrad, Ana; Gomez-Diaz, Julen; Lozano-Real, Garbiñe; Mugica-Errazquin, Itxaso; Patiño, Maria Jesus; Bidaurrazaga-Letona, Iraia; Irazusta, Jon; Gil, Susana María
Abstract: Background and Objectives: There is evidence that exercise interventions counteract the functional and cognitive decline experienced by long-term nursing home (LTNH) residents. To determine the most effective exercise intervention, we compared the effects of a multicomponent exercise intervention and a walking intervention on physical and cognitive performance, habitual physical activity, affective function, and quality of life among older adults living in LTNHs. Research Design and Methods: This 3-month single-blind randomized controlled trial (NCT03996083) involved 81 participants at 9 LTNHs randomly assigned to a multicomponent (MG) or a walking (WG) group. The MG participated in a twice-a-week individualized and progressive program composed of strength and balance exercises for 3 months. The WG was also individualized and participants walked up to 20 min per day. The primary outcome was the score on the short physical performance battery (SPPB). Secondary outcomes included other physical performance tests, habitual physical activity, cognitive performance, affective function, and quality of life. Results: Compared with the WG, the MG group showed greater improvements in physical performance, including the SPPB ( p < .05). No significant differences were observed in cognitive performance or habitual physical activity. Both groups showed improvements in anxiety and quality of life ( p < .05). Discussion and Implications: Although both interventions were effective in maintaining or improving affective function, the MG conferred greater improvements in physical function. Therefore, multicomponent interventions would be preferable over walking-only interventions. Otherwise, individualized and progressive walking interventions should be implemented to face the rapid decline in functionality encountered in LTNHs.